Minimax Shrunken Technique for Estimate Burr X Distribution Shape Parameter - Salman, Abbas Najim; Ameen, Maymona M.; Abdul-Nabi, A. E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The present paper concern with minimax shrinkage estimator technique in order to estimate Burr X distribution shape parameter, when prior information about the real shape obtainable as original estimate while known scale parameter. Derivation for Bias Ratio, Mean squared error and the Relative Efficiency equations. Numerical results and conclusions for the expressions mentioned above were displayed. Comparisons for proposed estimator with most recent works were made.